Potato production scenario and analysis of its total factor productivity in India - RANA, RAJESH K; ANWER, MD. EJAZ (The Indian Journal of Agricultural Sciences, 2018)
India is second largest producer of potatoes in the world after China. India showed tremendous growth in potato production during last one and half decade, however, this growth is led more by the area expansion than the yield enhancement. For further analysis on nature of productivity growth in Indian potato sector the computation of Total Factor Productivity (TFP) was done with the help of Malmquist Productivity Index (MPI). Year 2005 being the inflection point in the growth in Indian agriculture was used as period break year for this study and two periods, viz. pre-period (1997 to 2004) and post period (2005 to 2013) were considered for all analysis and descriptions. Bihar, West Bengal and Uttar Pradesh states constitute about 74% of Indian potato production hence, these states were assumed to represent Indian potato scenario. Except mild decline in potato productivity growth in Uttar Pradesh, area, production and productivity growth of potato showed acceleration in post-period compared to the pre-period in all the states. TFP improved in all the three states in post period however, in West Bengal the growth was negative (-2.3) even in the post period. Except Bihar where efficiency change was positive (1%) in pre-period, and further improved in post-period (2.1%), the efficiency change stagnated in all other cases. The TFP improvement in all the cases was either solely or mainly led by the technical change.